Svet vonjav v slovenskih uprizoritvenih umetnostih - Orel, Barbara (Amfiteater (Ljubljana), 2021)
The article provides an overview of performances on Slovenian stages that have used odour to stimulate the audience’s senses and arouse transformational effects. Representing the first research of this kind into Slovenian culture, the author demonstrates that odour was used as a means of sensory perception, especially in experimental theatre practices since the 1970s. One of the first such works was Cimetova vrata ladje norcev in druge spremembe (The Cinnamon Door of the Ship of Fools and Other Changes), a performance art piece directed by Tomaž Kralj at Glej Theatre in 1975. In the 1990s, the interest in olfactory perceptions grew among theatre-makers who successfully used odour to implement the aesthetics of the real in post-dramatic theatre and achieve the immersion of the spectator. This role of odour in theatre also continues in the 21st century. Barbara Pia Jenič began deliberately and continuously developing the poetics of scent at the Sensorium Theatre, which she founded in 2001 with Gabriel Hernandez. In her creation of sensorial events, Jenič relies on the methodologies of Enrique Vargas, with which she became acquainted as an actress and scent designer in his group Teatro de los Sentidos and creatively developed them at the Sensorium Theatre. As a scent designer, Jenič has collaborated with other Slovenian theatres, among others, on the 2015 operatorium, The Tenth Daughter (Deseta hči) by Svetlana Makarovič (based on the libretto by Milko Lazar, directed by Rocco) at the Slovenian National Theatre – Opera and Ballet Ljubljana.
Keywords: eksperimentalno gledališče; experimental theatre; gledališče Senzorium; odour; performing arts; post-dramatic theatre; postdramsko gledališče; sensorial theatre event; Sensorium Theatre; senzorialni gledališki dogodek; Slovenia; Slovenija; uprizoritvene umetnosti; vonj